Quantitative two-photon imaging of fluorescent biosensors - Yellen, Gary (Curr Opin Chem Biol, 2015)
Fluorescent biosensors are now routinely imaged using two-photon microscopy in intact tissue, for instance, in brain slices and brains in living animals. But most studies measure temporal variation – e.g., calcium transients in response to neuronal activity – rather than calibrated levels of biosensor occupancy (and thus levels of the sensed analyte). True quantitative measurements are challenging, since it is difficult or impossible to calibrate a sensor's dose-response in situ, and difficult to compare the optical signals from tissue to those during in vitro calibration. Ratiometric measurements (at two wavelengths) are complicated by variations in laser power and by wavelength-dependent attenuation in tissue. For some biosensors, fluorescence lifetime imaging microscopy (FLIM) provides a valuable alternative that gives well-calibrated measurements of analyte levels.